Growth of LiNb1-xTaxO3 solid solution crystals - Bartasyte, A; Glazer, A; Wondre, F; Prabhakaran, D; Thomas, P; Huband, S; Keeble, D; Margueron, S (2012)
The growth of single crystals of solid solutions of LiNbO 3 and LiTaO 3 has been studied by using a number of different techniques: Czochralski pulling, Top-Seeded Solution Growth, flux growth from LiBO 2 and LiVO 3, and by optical floating zone. Crystals with homogenous Li, Ta and Nb compositions were obtained by several techniques. Analysis of local and average compositions of Ta, Nb and Li by Raman spectroscopy, birefringence imaging and X-ray diffraction, in addition to EDAX, is described. The effects of replacing Nb by Ta and of Li non-stoichiometry on the lattice parameters and the compositional disorder over the whole composition range 0 ≤ x ≤ 1 are discussed. © 2012 Elsevier B.V. All rights reserved.